2018
DOI: 10.1177/2048872618795512
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of thrombus aspiration in ST-segment elevation myocardial infarction: an updated systematic review and meta-analysis of randomised clinical trials

Abstract: Background: The role of thrombus aspiration plus primary percutaneous coronary intervention in ST-segment elevation myocardial infarction remains controversial. Methods: We performed a meta-analysis of 25 randomised controlled trials in which 21,740 ST-segment elevation myocardial infarction patients were randomly assigned to thrombus aspiration plus primary percutaneous coronary intervention or primary percutaneous coronary intervention. Study endpoints were: death, myocardial infarction, stent thrombosis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
(125 reference statements)
0
10
0
Order By: Relevance
“…Despite its strong data and intuitive basis for incremental value of TA in hyperglycemic patients, results from pivotal trials and “real-world” registries of manual thrombectomy have not consistently demonstrated clinical benefits over standard PPCI in general population [ 20 , 26 , 27 ]. However, all these studies did not provide any evidence about the effects of TA in a subgroup of high-risk STEMI patients, such as those with hyperglycemia during the event.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its strong data and intuitive basis for incremental value of TA in hyperglycemic patients, results from pivotal trials and “real-world” registries of manual thrombectomy have not consistently demonstrated clinical benefits over standard PPCI in general population [ 20 , 26 , 27 ]. However, all these studies did not provide any evidence about the effects of TA in a subgroup of high-risk STEMI patients, such as those with hyperglycemia during the event.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared to Rabbani’s study, the DTBT in our no-LVT group was relatively short, which might potentially reduce the influence of delayed reperfusion. Although thrombectomy was not recommended in routine application [ 21 ], De Rosa, S. et al [ 22 , 23 ] showed that thrombectomy had important positive effects on long-term clinical outcome in high-risk patients with AMI, and its effect became relevant in late presenters, suggesting that thrombectomy might be helpful in selected subpopulations at higher clinical risk. However, in our study, patients who were treated with thrombectomy showed no significant difference in the occurrence of LVT.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data from an individual level meta-analysis including patients from the TAPAS, TASTE, and TOTAL trials suggested that some categories of patients such as those with a large thrombus burden may still benefit from TA [6]. In a recently published updated meta-analysis we have shown that the incidence of stroke in patients treated with TA is 0.84% compared to 0.59% observed in patients with no TA (number needed to harm 423) [8]. Although rare, the risk of stroke is real and we suggest to use TA only in cases of conventional PCI failure.…”
Section: Discussionmentioning
confidence: 91%